Feminism in Patriarchal Society Reflected in the Main Characters in Sabrina & Corina - Panggabean, Gloxzy Ruth; Gultom, Feriyanti Elina (TRANSFORM : Journal of English Language Teaching and Learning, 2024)
This study deals with feminism in patriarchal society based on the main character in anthology of short story named Sabrina & Corina by Kali Fajardo-Anstine. This research used qualitative descriptive as the method. The data of this study were dialogue and narratives that appeared in the story. The data was analyzed using Hannam’s (2007) theory. It was found that there are three definition of feminism found in the data, they are: 1) Recognition of imbalance power" found 11 data; 2) women's condition is a social construct found 8 data; 3) emphasizes women's autonomy found 5 data. From the data found, it can be seen that recognition of imbalance power is the definition of feminism that is most often found in these short stories. It shows that there is indeed a big difference in power and authority between men and women. The main characters in these stories also try to help, protect, and support other woman as their way to fight the patriarchy that already ingrained in society.